Evaluating an Expectation-Driven Question-Under-Discussion Model of Discourse Interpretation. Issue 3 (3rd April 2017) - Kehler, Andrew; Rohde, Hannah
Abstract : According to Question-Under-Discussion (QUD) models of discourse interpretation, clauses cohere with the preceding context by virtue of providing answers to (usually implicit) questions that are situated within a speaker's goal-driven strategy of inquiry. In this article we present four experiments that examine the predictions of a QUD model of interpretation when cast in terms of an integrated, expectation-driven model of discourse processing. The results of these studies together support the predictions of the model, demonstrating that contextual cues affect comprehenders' expectations about ensuing QUDs (Experiment 1), QUD expectations in turn influence the interpretation of discourse-dependent linguistic expressions (Experiment 2), and the biases associated with those expressions in turn influence the anticipation of QUDs (Experiments 3a and b).